MOTIVATIONAL EXPRESSIONS IN PRINCE EA’S YOUTUBE CHANNEL - Azzahra, Fadila Annisa; Yatmikasari, Ika (CALL, 2024)
This study investigates the use of expressive speech acts in the motivational spoken word performances of Prince EA. Expressive speech acts, which convey the speaker's emotions and attitudes, play a crucial role in persuasive and motivational communication. The aim was to understand how Prince EA effectively engages and inspires his audience through these acts. A qualitative analysis was conducted on a selection of Prince EA's spoken word performances. Using speech act theory as a framework, instances of expressive speech acts were identified and categorized. Data was collected through transcription and thematic analysis of the videos. The analysis revealed a significant presence of expressive speech acts in these performances that cover apologizing, condoling, lamenting, showing attitude, agreeing, using exclamation, wishing, and thanking. These acts were predominantly expressing hope, encouragement, empathy, and personal conviction. The frequent use of these expressions contributed to the emotional resonance and motivational impact of the performances. The findings suggest that the effective use of expressive speech acts enhances the motivational appeal of Prince EA's spoken word performances. By conveying genuine emotions and attitudes, a connection with the audience is created, fostering a sense of empathy and inspiration. Hence, this study highlights the importance of expressive speech acts in motivational speaking and offers insights for speakers aiming to engage and motivate their audiences effectively.Keyword: pragmatic, ethics, speech acts, motivation